The Role of Suggestions and Tips in Distorting a Third Party's Decision - Daniel Parra (Games, 2020)
This paper experimentally investigates the impact of suggestive messages and tipping on a third party's judgment. The experimental design uses a model with three players, wherein two players (A and B) create a joint project, and the third player (C) decides how to divide the project's earnings between the first two players. In two treatments, player B has an opportunity to influence player C's decision via a numeric message or an ex-post tip. The main finding of this paper is that giving player B the option to suggest a specific amount to the allocator does not increase his share. In contrast, when player C knows that player B can send him a tip, the share awarded to player B increases.
Additional information: APC was funded by the WZB and the Open Access fund of the Leibniz Association.
Keywords: 330; corruption; influence; reciprocity; tipping; lobbying